TOWARD A TOOL KIT FOR CURATING INDIGENOUS ART: A NON-INDIGENOUS FACILITATOR’S PERSPECTIVE - Griniuk, Marija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
This article explores the experiences of a non-Sámi project manager and educator working with a group of Sámi curators within a unique educational program designed for the Sámi community. Based on artistic research, this study focuses on the challenges and learning opportunities encountered, emphasizing the importance of cultural exchange and understanding in the field of Indigenous art and curating. It discusses strategies applied by the non-Sámi project manager, language barriers, and the role of hands-on activities in facilitating collaboration. The research provides insights into the broader context of Indigenous curatorial practices globally and highlights the need for mutual respect and adaptation for effective collaboration in educational programs. The study’s findings contribute to discussions on navigating cultural diversity within the context of Indigenous art and curating.